Safety profile of Methylphenidate under long-term treatment in Adult ADHD patients$cresults of the COMPAS Study - Kis, Bernhard; Lücke, Caroline; Abdel-Hamid, Mona; Heßmann, Philipp; Graf, Erika; Berger, Mathias; Matthies, Swantje; Borel, Patricia; Sobanski, Esther; Alm, Barbara; Rösler, Michael; Retz, Wolfgang; et al. (Pharmacopsychiatry, 2020)
Introduction The Comparison of Methylphenidate and Psychotherapy in adult ADHD Study (COMPAS) was a prospective, randomized multicenter clinical trial, comparing methylphenidate (MPH) with placebo (PLAC) in combination with cognitive behavioral group psychotherapy (GPT) or individual clinical management (CM) over the period of 1 year. Here, we report results on treatment safety. Methods MPH and PLAC were flexibly dosed. Among 433 randomized patients, adverse events (AEs) were documented and analyzed on an “as received” basis during week 0-52. Electrocardiogram data were recorded at baseline and week 24. Results Comparing 205 patients who received ≥1 dose of MPH with 209 patients who received PLAC, AEs occurring significantly more frequently in the MPH group were decreased appetite (22 vs. 3.8%), dry mouth (15 vs. 4.8%), palpitations (13 vs. 3.3%), gastrointestinal infection (11 vs. 4.8%), agitation (11 vs. 3.3%), restlessness (10 vs. 2.9%), hyperhidrosis, tachycardia, weight decrease (all 6.3 vs. 1.9%), depressive symptom, influenza (both 4.9 vs. 1.0%), and acute tonsillitis (4.4 vs. 0.5%). Syncope occurred significantly more often in the PLAC group (2.4 vs. 0%). Clinically relevant ECG changes occurred very rarely in both groups. Serious AEs were rare and without a significant group difference. The comparison of 206 patients treated with GPT versus 209 patients who received CM revealed no major differences. Serious AE classified as psychiatric occurred in 5 cases in the CM group and in 1 case in the GPT group. Conclusion In this so far longest-running clinical trial, methylphenidate treatment was safe and well-tolerated.